Pyrocarbon proximal interphalangeal joint arthroplasty - Mcguire, Duncan Thomas (University of Cape Town, 2015)
Arthritis of the proximal interphalangeal joint of the hand can be debilitating disease resulting in pain and stiffness. Treatment is initially conservative but with diseasse progression surgical treatment often becomes necessary. Arthroplasty is one of the surgical options available.